Implementasi Lagu “Rumah” Karya Salma Salsabil dan “Kembali Pulang” Karya Suara Kayu dan Feby Putri dalam Pengajaran Bahasa Indonesia bagi Penutur Asing (BIPA) - Efendi, Rachmat; Suyatno, Suyatno; Shodiq, Syamsul; Roni, Roni (Stilistika: Jurnal Pendidikan Bahasa dan Sastra, 2025)
This study aims to understand the use of the song "Rumah" written and performed by Salma Salsabil, and the song "Kembali Pulang," a collaborative work between Suara Kayu and Feby Putri, in Teaching Indonesian as a Foreign Language (BIPA). The main focus of this study is how these two songs can enhance Indonesian language skills, such as speaking, reading, listening, and writing, while also introducing Indonesian cultural values like togetherness, family bonds, and the longing for one's hometown. A qualitative approach with content analysis is employed to explore the application of these songs in BIPA learning. The song "Rumah" is suitable for beginner learners, while "Kembali Pulang" is more appropriate for intermediate to advanced learners. Both songs convey important messages about the values of family and the experience of being away from home in Indonesian social life. Through these songs, learners not only improve their language skills but also gain an understanding of emotional expressions in Indonesian, such as longing and exhaustion. Therefore, the use of songs as a media for BIPA learning proves to be an effective way to introduce both the Indonesian language and culture in an enjoyable and practical manner.